Clinical outcomes of conjugated linoleic acid supplementation in the overweight and the obese: a study protocol - Łochocka, Klaudia; Glapa, Aleksandra; Nowak, Jan Krzysztof; Duś-Żuchowska, Monika; Grabańska, Katarzyna; Bogdański, Paweł; Fidler, Ewa; Mądry, Edyta; Walkowiak, Jarosław (Journal of Medical Science, 2014)
This is the protocol of a study aiming to assess the impact of conjugated linoleic acid (CLA) on anthropometric parameters, body composition and densitometric parameters, carbohydrate and fat digestion and absorption, total energy expenditure, glucose and insulin homeostasis, lipid profile, adipokines concentrations, polyunsaturated fatty acids levels, markers of endothelial dysfunction and mineral status in humans. Seventy-four adult volunteers (BMI ≥ 25 kg/m2) will be randomized to receive 3.0 g of 80% CLA (50:50 cis-9, trans-11 and trans-10, cis-12 isomers) or 3.0 g of linoleic acid daily for 3 months. A range of parameters will be measured at baseline and after the intervention.